1990
DOI: 10.1007/bf00554820
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical genetic markers of squirrel monkeys and their use for pedigree validation

Abstract: Family data for 14 biochemical genetic markers fo squirrel monkeys (genus Saimiri) were derived from 73 pedigreed progeny and both parents of each, as well as from 16 additional progeny and one parent of each. The data for each marker and the phenotypic patterns were consistent with autosomal codominant inheritance. It was concluded from the genetic marker data that the pedigree records of seven progeny were incorrect. Retrospective investigations of colony records followed by typing of animals that might poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…However man, Aotus, and Cebus apella paraguayanus share at least one similar allele (GLO*2) that is, moreover, the most frequent one in any of these groups. Conversely, data from Leontopithecus (FORMAN et al, 1986) and Saimiri (VANDEBERG et al, 1990) do not allow us to establish comparisons of this kind due to the lack of interspecific standardizations.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However man, Aotus, and Cebus apella paraguayanus share at least one similar allele (GLO*2) that is, moreover, the most frequent one in any of these groups. Conversely, data from Leontopithecus (FORMAN et al, 1986) and Saimiri (VANDEBERG et al, 1990) do not allow us to establish comparisons of this kind due to the lack of interspecific standardizations.…”
Section: Resultsmentioning
confidence: 94%
“…Two GLO I alleles have also been reported in Saimiri (VANDEBERG et al, 1990), while in Leontopithecus, this locus was monomorphic (FORMAN et al, 1986). However, the recognition of shared glyoxalase I forms between Saimiri/Leontopithecus and man or a biochemical standardization of glyoxalase I based on the human electrophoretic patterns was not possible due to lack of human controls.…”
Section: Introductionmentioning
confidence: 89%
“…Biochemical markers have been used for pedigree validation in squirrel monkeys (VandeBerg et al 1990). Squirrel monkey infants are frequently carried by females in their social group other than by the real dam (allomaternal behavior).…”
Section: Importance Of Saimiri Species Identification and Pedigree Vamentioning
confidence: 99%
“…Genetic markers can be used to reliably distinguish between types of squirrel monkeys [43, 44, 52]. VandeBerg and colleagues [52] demonstrated that 14 biochemical genetic markers could be used to differentiate Guyanese squirrel monkeys from Bolivian or Peruvian monkeys, and to differentiate most Bolivian squirrel monkeys from most Peruvian squirrel monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic markers can be used to reliably distinguish between types of squirrel monkeys [43, 44, 52]. VandeBerg and colleagues [52] demonstrated that 14 biochemical genetic markers could be used to differentiate Guyanese squirrel monkeys from Bolivian or Peruvian monkeys, and to differentiate most Bolivian squirrel monkeys from most Peruvian squirrel monkeys. Thus, while breeding colonies can be structured from animals matched for clearly defined geographic origin (and hence of uniform subspecies composition), genetic marker assessments will be of substantial value in selecting animals for either breeding colonies or research sample groups.…”
Section: Introductionmentioning
confidence: 99%